The Mongol conquests : AD 1200-1300 - Time-Life Books (Amsterdam : Time-Life Books, 1989)
1. Mongol--History. 2. China--History--Yuan dynasty, 1260-1368.
Includes bibliographical references.
Bibliography: p. 170-171.
Basic Ed. Students
Keywords: Mongols -- History; China -- History -- Yuan dynasty, 1260-1368.